Healing in the Homeland: Haitian Vodou Tradition - Armand, Margaret Mitchell (Lexington Books, 2013)
Margaret Mitchell Armand presents a cutting edge interdisciplinary terrain inside an indigenous exploration of her homeland. Her contribution to the historiography of Haïtian Vodou demonstrates the struggle for its recognition in Haïti’s post-independence phase as well as its continued misunderstanding. Through a methodological, original study of the colonial culture of slavery and its dehumanization, Healing in the Homeland: Haitian Vodou Traditions examines the sociocultural and economic oppression stemming from the local and international derived politics and religious economic oppression. While concentrating the narratives on stories of indigenous elites educated in the western traditions, Armand moves pass the variables of race to locate the historical conjuncture at the root of the persistent Haïtian national division. Supported by scholarships of indigenous studies and current analysis, she elucidates how a false consciousness can be overcome to reclaim cultural identity and pride, and include a sociocultural, national educational program, and political platform that embraces traditional needs in a global context of mutual respect. While shredding the western adages, and within an indigenous model of understanding, this book purposefully brings forth the struggle of the African people in Haïti.